The appendix "mucocoele" misnomer: radiological terminology of "likely appendix mucinous neoplasm" better reflects pathology findings. Issue 3 (March 2023) - Bhagwanani, A.; El-Sheikha, J.; Shah, N.; Thrower, A.; Carr, N.J.; Moran, B.J.
Abstract : AIM: To review the radiological terminology used to describe dilated mucin-containing appendiceal lesions with correlation to the histopathological diagnosis. MATERIALS AND METHODS: Radiology and histopathology reports for all patients with an abnormally dilated appendix referred to a tertiary peritoneal malignancy centre, between January 2021 and December 2021, were reviewed. RESULTS: Overall, 213 patients were included with a median appendiceal diameter of 25.5 mm (range 10–125 mm). Peritoneal disease was present in 109 patients, with the remaining 104 cases demonstrating a dilated appendix only. Local radiology reports were available for 201 cases with the appendix described in 168 cases as appendiceal mucocoele ( n= 104), appendiceal neoplasm ( n= 40), appendicitis ( n= 18), and dilated appendix ( n= 6). The appendix was not mentioned in 33/201 (15%), either misinterpreted as other pathology ( n= 15) or not reported ( n= 18). Peritoneal malignancy histopathology reports were available in 188 cases and reported as low-grade appendix mucinous neoplasm (LAMN, n= 144), high-grade appendix mucinous neoplasm (HAMN, n= 13), LAMN with foci of HAMN ( n= 2), LAMN with neuroendocrine tumour ( n= 2), LAMN with goblet cell adenocarcinoma (n=1), goblet cell adenocarcinoma ( n= 8), mucinous adenocarcinoma ( n= 14), non-mucinous adenocarcinoma ( n= 1), and benign histology ( n= 3). Only one case of a true inflammatory "mucocoele"/retention cyst was reported. CONCLUSION: In this cohort of patients, the overwhelming majority of dilated, mucin-filled appendices contained malignant cells and benign mucin-filled appendices were rare. The present authors advocate that the term "likely appendix mucinous neoplasm" should replace "appendix mucocoele" to represent the most likely pathology and facilitate less ambiguous interpretation in management decisions. Highlights: The term mucocoele is a non-specific macroscopic descriptor of a dilated appendix. The majority of dilated appendices harbour malignant cells. The term "likely mucinous appendix neoplasm" better reflects likely pathology. Left untreated, mucinous appendix neoplasms can result in pseudomyxoma peritonei.